Cohort Profile: The Mexican Health and Aging Study (MHAS) - Wong, Rebeca; Michaels-Obregon, Alejandra; Palloni, Alberto (International journal of epidemiology, 2017)
The Mexican Health and Aging Study (MHAS) was designed to prospectively evaluate the impact of disease on the health, function and mortality of adults over the age of 50 in both urban and rural areas of Mexico. The overall goal of the study is to examine the ageing process and its disease and disability burden in a large representative panel of older Mexicans, using a wide socioeconomic perspective. The study protocols and survey instruments are highly comparable to the U.S. Health and Retirement Study (HRS).The MHAS 2001 baseline is a nationally and urban-rural representative survey of individuals born in 1951 or earlier. Three waves of data have been collected so far: baseline in 2001 and follow-ups in 2003 and 2012. In 2012, the study added a representative sample of the population from the 1952-62 birth cohorts. A fourth wave will be collected in 2015.The data files and documentation are available free of charge at the study website [www.MHASweb.org] in English and [www.ENASEM.org] in Spanish.